(untitled) - Nguema Mve, Oliver Patrice

Petrology, geochronology and provenance of the Laingsburg and Tanqua Karoo submarine fan systems, Ecca Group, South Africa (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Earth Sciences))—University of Stellenbosch, 2005.